1994
DOI: 10.1159/000217887
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation by Soluble Factors from Tumor Cells Cultured in vivo in Diffusion Chambers

Abstract: The delayed-type hypersensitivity (DTH) response and lymphocyte-mediated angiogenesis were determined in mice bearing in vivo cultures of mammary tumor cells in diffusion chambers (DCs). Soluble tumor products which diffuse from the DCs were able to stimulate the immune system for both the DTH reaction and angiogenic activity by spleen cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Stillstom demonstrated anti‐tumor immunity in a different tumor model; but the protection observed was transient: the levels of protection dropped dramatically with time 29 . In other cases no systemic immunity was observed 30,31 ” and in at least one case it was argued that the presence of diffusion chambers containing tumor cells could lead to enhanced tumor growth 31 …”
Section: Tumor Immunotherapy Using An Immunoisolation Devicementioning
confidence: 99%
“…Stillstom demonstrated anti‐tumor immunity in a different tumor model; but the protection observed was transient: the levels of protection dropped dramatically with time 29 . In other cases no systemic immunity was observed 30,31 ” and in at least one case it was argued that the presence of diffusion chambers containing tumor cells could lead to enhanced tumor growth 31 …”
Section: Tumor Immunotherapy Using An Immunoisolation Devicementioning
confidence: 99%
“…Tumor cell suspensions were prepared by an enzy matic method [9], Briefly, 1-rr.m3 tumor grafts were treated for 30 min at 37°C with 0.001% Streptomyces griseus Pronase P (Sigma) and 0.0035% DNAase I (Sigma). Tumor cell suspensions were washed three times with serum-free medium, and only cell suspen sions with an overall viability superior to 80%, as determined by the trypan blue exclusion test, were used.…”
Section: Preparation O F Tumor Cell Suspensionsmentioning
confidence: 99%
“…The DC system enables the study of different host responses to soluble products released by tumor cells actively growing with in the DC and consequently the study of tumor cell alterations occurring in vivo [8], We have previously reported that tumor cells growing within DC could modulate the host's delayed-type hypersensitivity and lympho cyte-dependent angiogenesis response to solu ble tumor extracts [9]. Thus, it is of extreme importance to determine which tumor-de rived factors can mediate immune responses of the host and how they can modulate tumor growth and metastasis development [10].…”
Section: Introductionmentioning
confidence: 99%
“…Solid tumors grow in part by secreting angiogenic factors that promote neovascular ization, thus supplying the tumor with oxygen, nutrients and growth factors [2][3][4], Tumor metastasis is a multistep process that also includes angiogenesis [5,6]. Recently, we could achieve inhibition of tumor growth and metastasis outcome using an inhibitor of tumor-and lymphocyteinduced angiogenesis [7], It is well known that when immunocompetent lympho cytes are injected intradermally into allogeneic mice, they evoke a complex angiogenic response called 'lymphocyteinduced angiogenesis' [8], Activated lymphocytes release soluble mediators (lymphokines) that may act directly on endothelial cells or indirectly on macrophages, being the appropriate stimulus for host endothelial response, thus acting as angiogenic factors [9,10], We have previously demonstrated that spleen lymphocytes from tumor-bear ing mice induced a strong neovascular response even in syngeneic combination (SLIA) [11], Subsequently we re ported that T lymphocytes were the main spleen popula tion responsible for this neovascular response [12].…”
Section: Introductionmentioning
confidence: 99%